The New Normal? The European Union’s Temporary Frameworks for State Aid - Kociubiński, Jakub (University of Wroclaw. Faculty of Law, Administration & Economics, 2024)
It is widely agreed that the global economy has entered a phase of heightened uncertainty. Since all downturns and slowdowns involve low aggregate demand, the authorities typically step in by increasing their own spending to protect businesses and jobs. During the Covid pandemic the European Union has witnessed an unprecedented level of State aid measures, under the hastily adopted dedicated temporary framework. Temporary rules have also been adopted to facilitate State aid supporting companies affected by the Russian invasion of Ukraine, which are still in force today (March 2023). The common pattern of crisis responses in turn allows for a more general, non-event-specific, assessment of State aid measures taken to reduce economic disturbances. Sufficient time has now passed for an attempt to take stock of these efforts. This paper therefore seeks to assess State aid measures designed to remedy serious economic disruptions, identify their weak points and recommend improvements. The analysis, preceded by a succinct description of the European Union’s State aid toolbox for crisis aid, will focus on the previously identified potential problem areas: How to determine whether an aid measure is indeed capable, in itself, of remedying the serious disturbance in the economy, especially when it is granted to a single undertaking, and how to ensure the effectiveness of State aid control. The paper will conclude with a set of recommendations.
Keywords: state aid; temporary framework; crisis aid; disaster aid; economic disturbance